Adenoviral transfer of hemopexin gene attenuates oxidative stress and apoptosis in cultured primary cortical neuron cell exposed to blood clot. Issue 15 (14th October 2020) - Liu, Yi; Tan, Changhong; Li, Weina; Liu, Xi; Wang, Xin; Gui, Yuejiang; Qin, Lu; Deng, Fen; Hu, Changlin; Chen, Lifen
Abstract : Background: A growing body of experimental evidence suggests that hemin released from heme is a potent oxidant and accumulates in intracranial hematomas. Hemopexin (Hpx) decreases hemin accumulation and catabolism by nerve cells. In previous study, we observed that Hpx gene knockout aggravated striatal injury and worsened behavioral deficits of mice subjected to intracerebral hemorrhage. Aim: To examine the effect of Hpx on oxidative damage and apoptosis in cultured nerve cells with blood clot. Methods: Neuron and glial cells were transfected with adenoviral Hpx gene. Transfected primary neuron-glial cells were co-cultured with 50 μl of arterial blood clot using insert transwells. The sham group was co-coulture with 50 μl of DMEM/F12, which contained 28 μl of serum; the control group was transfected with adenoviral vector. At 12 and 24 h, the level of malonaldehyde (MDA), surperoxide dismutase (SOD) concentration, glutathione (GSH), apoptosis, expression of HO-1 and caspase-3 were detected. Results: MDA level was decreased ( P < 0.01) whereas SOD and GSH concentration were increased in the Hpx group ( P < 0.05 and P < 0.01, respectively). Results of flow cytometry revealed no significant difference in apoptosis between the Hpx group and model group at 12 h. However, the percentage of cells undergoing apoptosis in the Hpx group was decreased at 24 h compared with the model group ( P < 0.01). HO-1 expression decreased in the Hpx group at 24 h ( P < 0.01) while caspase-3 expression decreased at both 12 and 24 h ( P < 0.011 and P < 0.05, respectively) compared with the model group. Conclusion: Hpx protected nerve cells exposed to blood from injury by anti-oxidation and a decrease in the expression of HO-1 and caspase-3.